Efektivitas Media Pembelajaran Macromedia Flash Terhadap Hasil Belajar Siswa pada Materi Bilangan Bulat dan Pecahan Kelas VII - Rizayanti (Jurnal Aktual Pendidikan Indonesia, 2022)
Learning media serves to convey subject matter so that it is easily understood by students. The success of the learning process is the main thing that is coveted in carrying out education in schools. The research objective is whether the use of Macromedia flash learning media is effective to improve student learning outcomes. The research method uses a quantitative approach, with the type of experimental research, the results of the research are for the experimental class there is an increase in learning outcomes, after being given treatment, namely the application of macromedia flash learning media, before treatment 8 students got the lowest score of 20 and the highest score of 3 students was 55 , whereas after being given treatment the student scores were above average while the control class showed that there was no significant change in student learning outcomes in the control class, the control class was a class that did not use macromedia flash learning media, so the results were very different from the experimental class. Then macromedia flash is one of the effective media that must be applied by the teacher. During the teaching and learning process The success of the teaching and learning process is supported by various parties in it, both students and teachers.